Career Selection: Framing, Groupthink, and Financial Rewards in Accounting: Pemilihan Karier: Framing, Groupthink, dan Imbalan Finansial dalam Studi Akuntansi - Fitria Novita Sari; Imelda Dian Rahmawati (Academia Open, 2023)
This research aims to examine the impact of framing, groupthink, and financial rewards on career selection decisions among accounting students at UMISIDA. The study included 38 active students from the accounting faculty as respondents. Statistical analysis was conducted using the SPSS 20 program, including validity and reliability tests. The findings revealed that framing partially had a positive influence on career selection decisions, with a regression score of 0.233. Moreover, groupthink positively affected career selection decisions, with a regression score of 0.961. When considered together, framing, groupthink, and financial rewards significantly influenced career selection decisions, with a significant level of 0.000 < 0.05. Therefore, it can be concluded that the research hypothesis is supported. This study sheds light on the factors that play a crucial role in career decision-making among accounting students, providing implications for academic institutions and career counselors in enhancing career guidance and decision-making processes. Highlights: Framing: Investigating the influence of framing on career selection decisions in the field of accounting studies. Groupthink: Examining the role of groupthink in shaping career selection decisions among accounting students. Financial rewards: Assessing the impact of financial rewards on career selection choices in the context of accounting studies. Keywords: framing, groupthink, financial rewards, career selection, accounting studies